ANALISA PENGARUH SUDUT SERANG S1223 PADA LAMBUNG BIS AIR TERHADAP GAYA ANGKAT KAPAL - Addien Loka Kirana (2021)
Ships are sea transportation that is affected by the use of fuel when operating. The reduced fuel consumption is influenced by the small value of a ship's resistance. The use of hydrofoil aims to reduce drag when the ship is sailing at high speed. The water bus is a sea transportation that requires high speed when operating. The analysis was carried out using foil on the hull of the HYSUCAT catamaran water bus using variations in angles of attack 0, 5, 10, 15 degrees with the CFD method on the Ansys and Maxsurf applications. an optimal angle of attack for use on waterbus hulls. Then use five variations of speed to determine the value of the smallest ship resistance.